The Effect of Global and National Value Chains on Environmental Innovation and Research and Development: An Analysis of Ibovespa Companies - Ferreira Benedito Gomes Rocha, Lucas; Rizzi, Denise Isabel; Teixeira da Silva, Crisiane; Emil Hoffmann, Valmir (Review of Business Management, 2023)
Purpose – To analyze the effect of national and global value chains on environmental innovation and research and development in the context of Brazilian companies listed on the Ibovespa. Theoretical framework – Value chain and open innovation. Design/methodology/approach – This is descriptive, documentary research that uses a quantitative approach, through the analysis of secondary data extracted from Refinitiv Eikon. The research population consisted of 70 non-financial companies listed on the Ibovespa between the years 2016 and 2020. Findings – The global value chain affects environmental innovation and research and development (R&D) in a positive and significant way, revealing that companies with more evidence in their reports on formalizations with suppliers and customers show improvements in their environmental products with ecological designs and carry out more R&D spending. Those companies that have, in addition to national connections, connections with companies from other countries are more likely to have greater capacity for innovation. Practical & social implications of research – The research helps in understanding how organizations can improve their value chain, considering geographic aspects and interorganizational relationships, providing more assertively innovative resources. Originality/value – Although a national value chain does not influence any increase in environmental innovation, it does impact higher R&D spending. As eco-innovation involves voluntary disclosure, it is inferred that companies that are limited to maintaining relationships in Brazil do not receive the same institutional pressure, when compared to companies with a global value chain, since the latter are connected with firms in countries with greater enforcement mechanisms regarding sustainable practices. Keywords: global and national value chain, environmental innovation, research and development, Ibovespa.